INCREASED DURABILITY OF FRICTION UNITS IN OIL AND GAS INDUSTRY - Гнип, Марія Михайлівна; Криштопа, Людмила Іванівна; Криштопа, Святослав Ігорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article is devoted to decrease of durability of dynamic and thermal loading of band-block brakes of drilling hoists of drill units at the expense of usage new type of a band-block brake with multipair friction units. The mathematic description of dynamic processes at the beginning and second stages of braking of a new type of a brake is made and the analytical dependences for definition its main operation and design parameters are obtained: friction forces, efforts of pulls filling and unfilling of branches of a band, brake moments. As a result of the held experimental researches of a new brake are obtained: legitimacies of change of unit loads, surface temperatures, friction coefficients, wear of external and internal surfaces of frictional sites of a brake; legitimacies of influencing of static and dynamic coefficients of a mutual overlap internal and external pairs of abrasion on values of friction forces, friction coefficients, surface temperatures and braking time at different stages.